Relative changes to heirs’ property: a national assessment based on residential property records - J. Wesley Burnett; Clayton Winters-Michaud (Agricultural and Resource Economics Review)
Heirs’ property is a form a land tenure that can negatively impact landowners, particularly those who want to use their land for agricultural purposes. Over the past decade there has been an increase in legal reforms and assistance programs aimed at addressing issues associated with heirs’ property. Yet, this phenomenon has received little attention in the applied economics literature. With the aim of motivating future economic research, we make the following two contributions. First, we synthesize the existing multi-disciplinary literature on heirs’ property into an economically tractable framework. Second, we use parcel-level tax record data from 2015 and 2021 to track changes to the amount of heirs’ property over time and examine its rate of formation net of land leaving heirs’ property. We examine the changes to heirs’ property on non-agricultural and agricultural parcels (and the number of acres of land within parcels) separately. We find that the total number of parcels and acres, on non-agricultural lands, declined by about one percent and six percent, respectively. Whereas, acreage on heirs’ property agricultural lands decreased by about two percent. These small changes mask large transitions in and out of heirs’ property. Our estimates suggest that the formation of heirs’ property persists today and offsets most of the reductions obtained from land leaving heirs’ property. Additional analysis reveals significant heterogeneity across regions and localities.